[I217] Implementation and practical experience with the new Euratom directive occupational dose limit to the lens of the eye: From 150 MSV to 50 MSV per year. (August 2018) - Martin, Colin
Abstract : Purpose: The reduction in dose limit for the lens of the eye has focussed attention on methods for protecting the eyes of interventional radiologists and cardiologists. The need to obtain reliable dose measurements while protecting the eye, sometimes by using protective eyewear is proving a particular issue. This paper will explore some of the factors and consider options available. Methods: The International Commission on Radiological Protection are finalising a report on "Occupational Radiological Protection in Interventional Procedures" to provide guidance on some of the issues and the main conclusions relating to eye dose will be presented. In addition results from studies involving the investigation of shielding provided by different protection methods, including results from practical studies and computer simulations, will be reviewed. Different options for measurement of eye doses will be considered. Results: Ceiling suspended screens provide effective shielding for the whole head and if used efficiently they can reduce eye doses to levels well below the dose limit. However, this requires the operator to make adjustments to the screen whenever the patient couch or X-ray tube position are changed. Protective eyewear provides additional shielding, but its use complicates measurement of dose to the eye lens. Factors relating to the effectiveness of eyewear of varying design will be considered, and flaws in current models highlighted. When lead glasses are worn, the dose to the eye lens would ideally be measured by a dosimeter placed on the skin, near to the eye, and behind the lead glasses. Dosemeters could be attached to the glasses, but this has its own problems and if located in certain positions, dosemeters could significantly underestimate doses to the eyes. Alternatively dosemeters could be worn on the side of the head or forehead, but then a correction factor would need to be applied to obtain the actual dose to the eye. Conclusions: It should be possible to keep doses to the eyes for interventional radiologists and cardiologists below the dose limit with effective use of protective devices. However, eye dosimetry will be problematic and users need to understand the problem if this is to be accomplished.